1992
DOI: 10.1002/bies.950140704
|View full text |Cite
|
Sign up to set email alerts
|

How the EcoRI endonuclease recognizes and cleaves DNA

Abstract: One popular recombinant DNA tool is the EcoRI endonuclease, which cleaves DNA at GAATTC sites and serves as a paradigm for sequence specific DNA-enzyme interactions. The recently revised X-ray crystal structure of an EcoRI-DNA complex reveals EcoRI employs novel DNA recognition motifs, a four alpha-helix bundle and two extended chains, which project into the major groove to contact substrate purines and pyrimidines. Interestingly, pyrimidine contacts had been predicted based on genetic and biochemical studies.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 74 publications
0
43
0
1
Order By: Relevance
“…Different mechanisms have been proposed for the action of class II restriction endonucleases: either the reactions can occur simultaneously on each strand, or the two reactions occur sequentially, with or without the release of an intermediate. Several mechanistic studies have revealed that EcoRI usually cuts both strands sequentially without releasing an intermediate, and that the dissociation of the final product is the rate-limiting step (23,24), although altered reaction kinetics have been observed that depend on the substrate characteristics as well as on the assay conditions (24-29). The method described in this study detects cleavage reactions by observing the separation of two different fluorescent labels, resulting from scissions in both strands of a single molecule; consequently, the kinetics that is observed refers to an overall reaction rate.…”
Section: Resultsmentioning
confidence: 99%
“…Different mechanisms have been proposed for the action of class II restriction endonucleases: either the reactions can occur simultaneously on each strand, or the two reactions occur sequentially, with or without the release of an intermediate. Several mechanistic studies have revealed that EcoRI usually cuts both strands sequentially without releasing an intermediate, and that the dissociation of the final product is the rate-limiting step (23,24), although altered reaction kinetics have been observed that depend on the substrate characteristics as well as on the assay conditions (24-29). The method described in this study detects cleavage reactions by observing the separation of two different fluorescent labels, resulting from scissions in both strands of a single molecule; consequently, the kinetics that is observed refers to an overall reaction rate.…”
Section: Resultsmentioning
confidence: 99%
“…The question of whether protein conformational changes occur during EcoRI catalysis has been unresolved for several years (10,57,58). The magnitude of the activation volumes for catalysis at both GAATTC and TAATTC sites clearly indicates that significant conformational changes do occur during the catalytic steps of the reaction (48,59).…”
Section: Biochemistry: Robinson and Sligarmentioning
confidence: 99%
“…Restriction endonucleases, for example, are DNA-binding proteins whose catalytic functions are inactive on nonspecific DNA and active at specific sites. Allosteric effects of DNA sequence on endonuclease activity have been proposed for EcoRI (Heitman 1992) and demonstrated for NaeI, NarI, BspMI, HpaII, and SacII (Oller et al 1991).Might the activities of transcriptional regulatory proteins similarly be governed or influenced by the DNA sequences to which they bind? The magnitude of activation or repression by a given factor commonly varies ~These authors contributed equally to this work.…”
mentioning
confidence: 99%
“…Restriction endonucleases, for example, are DNA-binding proteins whose catalytic functions are inactive on nonspecific DNA and active at specific sites. Allosteric effects of DNA sequence on endonuclease activity have been proposed for EcoRI (Heitman 1992) and demonstrated for NaeI, NarI, BspMI, HpaII, and SacII (Oller et al 1991).…”
mentioning
confidence: 99%